Relationship with God as a Secure Base in Relational Psychotherapy - Barbara Simonič (Bogoslovska Smotra)
The formation of a secure and safe attachment relationship with God is an essential element in the process of religious coping with distress. This is a crucial aspect that must be integrated into the psychotherapeutic process. This paper presents an interdisciplinary approach that emphasises the importance of the spiritual element in therapeutic work. It draws on the theoretical foundations of attachment theory and religious coping to explore how a relationship with God can become a safe starting point in relational psychotherapy and how spirituality can be integrated into the therapeutic process. In doing so, it opens up a discussion on the relationship between faith, psychological well-being and effective therapeutic approaches that can enrich the understanding and practice of relational psychotherapy.